Tun Abdullah Ahmad Badawi remains at the heart of the faculty of pharmacy, UiTM Bertam campus - Che Lamin, Roz Azinur; Othman, Nursyuhadah; Karuppannan, Mahmathi (Faculty of Pharmacy, 2025)
In honour of Tun Abdullah Ahmad Badawi’s contributions, a programme titled “Remembering State Minister Tun Abdullah Ahmad Badawi: Father of Human Capital Development” was held on 19 September 2025 at Bertam Resort & Water Park, Kepala Batas, Pulau Pinang. It was a special program organised by the Ministry of National Unity and the National Archives of Malaysia in conjunction with Malaysia Day 2025. This programme aimed to showcase and document the achievements, leadership, and legacy of Malaysia’s fifth Prime Minister, Tun Abdullah Ahmad Badawi, who was affectionately referred to as the Father of Human Capital Development [2]. In the past, Kepala Batas was just a “cowboy town” surrounded by oil palm plantations. However, the achievements observed today are a culmination of meticulous planning and efforts by the late Tun [3]. The result of Tun's dedication that is closest to our hearts is the establishment of Kepala Batas as an education hub, exemplified by the presence of Universiti Teknologi MARA, Bertam Campus, and the establishment of the Faculty of Pharmacy. The Faculty of Pharmacy at Bertam Campus is the only branch campus, with the main faculty located at Puncak Alam, Selangor. The Faculty of Pharmacy, Bertam Campus, aims to produce graduates with a Diploma in Pharmacy. Other developments in the Kepala Batas area include the establishment of educational institutions such as MARA Junior Science College (MRSM), Kepala Batas Science Secondary School, the Advanced Medical & Dentistry Institute of Universiti Sains Malaysia (USM), the Industry Training Institute and Nursing College [3]. Therefore, we must acknowledge that the legacy of the late Tun Abdullah extends beyond his contributions to educational development; it has also significantly influenced the local and national economic sectors. His efforts have attracted investors to Kepala Batas, particularly in the realms of business and tourism. Furthermore, it is crucial for us to foster a spirit of patriotism, unity, and greater appreciation for our national leaders, especially among the younger generation.